Penerapan Cooperative Learning Tipe Think Pair Share untuk Meningkatkan Hasil Belajar dan Keterlibatan Siswa dalam Pembelajaran Matematika - Wahyuni, Sri; Purnama, Eka Desy; Budiman, Januar (Universitas Batanghari Jambi, 2025)
The Cooperative Learning model of Think Pair Share type to improve learning outcomes and student engagement in learning mathematics at Dharma Mulya Christian High School Surabaya. The subjects of this study were 20 students consisting of 11 female students and 9 male students. This research uses the Kemmis and McTaggart method through 2 cycles. Initial data showed that none of the students' involvement was located at the High level, there was 1 student at the Moderate level, 12 students at the Low level and there were 7 students at the Very Low level. From the written test to determine the learning outcomes of 20 students, only 4 students scored above the KKM, there were 16 students who did not meet the KKM or 80% of students' scores did not meet the specified standards. The final results of Cycle 1 and Cycle 2 for student engagement there was no one in the Very Low category, there were 2 students in the Low category, the Moderate category increased, namely there were 15 students, and the High category had 3 students. Likewise, for student learning outcomes at the end of cycles 1 and 2, 17 students reached the KKM or the percentage reached 85%, so that the research has reached the success indicator. This study found that the application of Cooperative Learning type Think Pair Share can improve learning outcomes and student involvement in learning mathematics.